Analysis of Real Costs and INA-CBG of Hyperthyroidism in Hasanuddin University Hospital - Suyanto; Siti Saharah Abdullah; Amelia Lorensia (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Hyperthyroid disease requires continuous treatment with not cheap medicalcosts. For JKN participants, the cost of treating hyperthyroidism has been fullycovered by BPJS through the INA-CBG package. However, there is often amismatch between the INA-CBG package and the real hospital costs thus causinglosses for the hospital. This research is a comparative study with a hospitalperspective and the purpose of this study is analyze difference between directmedical cost of hospitals and INA-CBG package for the treatment of JKNoutpatient hyperthyroidism patient in Hasanuddin University Hospital (RSUH)Makassar using data from January 2017 to December 2018. Data collection wascarried out by retrospective observational and data analysis using statistical non-parametric tests. The results showed that INA-CBG package cannot cover allcomponents of the costs of treating hyperthyroid disease. The laboratory cost hasa proportion of 83% of the total medical cost, which is an average of IDR465.683,70 every patient. Meanwhile, the INA-CBG rate with code Q-5-44-0 onlycovers medical expenses of IDR 185.500 every patient. The conclusion of thisstudy shows that there is a negative difference (-) between the real cost of thehospital and the INA-CBG rate, which is IDR 34.406.900,00 and an average of IDR373.988.04 every patient. The recommendation is related to adjustment of theINA-CBG rate to cover the riil costs.